2017
DOI: 10.3892/br.2017.970
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of the diagnostic efficacy of plasmic methylated septin-9 as a novel biomarker for colorectal cancer

Abstract: Abstract. The methylation status of septin-9 gene in plasma has been developed as a promising biomarker to aid in the diagnosis of colorectal cancer (CRC). In this study, we aimed to evaluate the overall diagnostic ability of septin-9 methylation for detection of CRC. Studies on the diagnostic performance of plasma septin-9 in CRC were searched from the online databases up to January 31st, 2017. Risk of bias among the studies was estimated according to the Quality Assessment of Studies of Diagnostic Accuracy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…However, clinical compliance of this stool-based test was low because of its inconvenience and requirement of repeated tests [ 27 ]. The sensitivity of plasma mSEPT9 for CRC using 2/3 algorithm in our study is consistent with the data in a quantitative meta-analysis by Zhang et al [ 36 ], which showed that plasma mSEPT9 sustained a pooled sensitivity of 64% (95% CI: 59%–68%) for CRC detection in the Asian-based population. Previous studies showed that the 1/3 algorithm draws higher sensitivity and lower specificity than the 2/3 algorithm in mSEPT9 test, with the sensitivity ranging from 68% (95% CI: 53% -80%) to 95.6% (95% CI: 89.2%–98.8%) for CRC detection [ 6 , 37 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, clinical compliance of this stool-based test was low because of its inconvenience and requirement of repeated tests [ 27 ]. The sensitivity of plasma mSEPT9 for CRC using 2/3 algorithm in our study is consistent with the data in a quantitative meta-analysis by Zhang et al [ 36 ], which showed that plasma mSEPT9 sustained a pooled sensitivity of 64% (95% CI: 59%–68%) for CRC detection in the Asian-based population. Previous studies showed that the 1/3 algorithm draws higher sensitivity and lower specificity than the 2/3 algorithm in mSEPT9 test, with the sensitivity ranging from 68% (95% CI: 53% -80%) to 95.6% (95% CI: 89.2%–98.8%) for CRC detection [ 6 , 37 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…47 A meta-analysis of studies of this assay found a pooled sensitivity of 67% and specificity of 89% for detection of CRC. 48 Capsule colonoscopy involves ingestion of a large pill-sized camera that records images during its transit through the intestine. Highly effective bowel preparation is required, typically involving use of booster doses and/or a prokinetic agent.…”
Section: Direct Visualizationmentioning
confidence: 99%
“…Additionally, four studies included in this meta-analysis were assessed as having a high probability of patient selection bias and could not include research reported since 2017. Two other meta-analyses5 6 did not conduct a comprehensive analysis of diagnostic accuracy of mSEPT9 tests: the first study5 considered covariates to assess sources of heterogeneity but provided limited evidence of the effect of those covariates on the diagnostic efficacy of mSEPT9. The second study6 only provided estimates on sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%